G-quadruplexes Stabilization Upregulates CCN1 and Accelerates Aging in Cultured Cerebral Endothelial Cells - Noh, Brian; Blasco-Conesa, Maria P.; Lai, Yun-Ju; Ganesh, Bhanu Priya; Urayama, Akihiko; Moreno-Gonzalez, Ines; Marrelli, Sean P.; McCullough, Louise D.; Moruno-Manchon, Jose Felix (Frontiers in Aging, 2022)
Senescence in the cerebral endothelium has been proposed as a mechanism that can drive dysfunction of the cerebral vasculature, which precedes vascular dementia. Cysteine-rich angiogenic inducer 61 (Cyr61/CCN1) is a matricellular protein secreted by cerebral endothelial cells (CEC). CCN1 induces senescence in fibroblasts. However, whether CCN1 contributes to senescence in CEC and how this is regulated requires further study. Aging has been associated with the formation of four-stranded Guanine-quadruplexes (G4s) in G-rich motifs of DNA and RNA. Stabilization of the G4 structures regulates transcription and translation either by upregulation or downregulation depending on the gene target. Previously, we showed that aged mice treated with a G4-stabilizing compound had enhanced senescence-associated (SA) phenotypes in their brains, and these mice exhibited enhanced cognitive deficits. A sequence in the 3’-UTR of the human CCN1 mRNA has the ability to fold into G4s in vitro. We hypothesize that G4 stabilization regulates CCN1 in cultured primary CEC and induces endothelial senescence. We used cerebral microvessel fractions and cultured primary CEC from young (4-months old, m/o) and aged (18-m/o) mice to determine CCN1 levels. SA phenotypes were determined by high-resolution fluorescence microscopy in cultured primary CEC, and we used Thioflavin T to recognize RNA-G4s for fluorescence spectra. We found that cultured CEC from aged mice exhibited enhanced levels of SA phenotypes, and higher levels of CCN1 and G4 stabilization. In cultured CEC, CCN1 induced SA phenotypes, such as SA β-galactosidase activity, and double-strand DNA damage. Furthermore, CCN1 levels were upregulated by a G4 ligand, and a G-rich motif in the 3’-UTR of the Ccn1 mRNA was folded into a G4. In conclusion, we demonstrate that CCN1 can induce senescence in cultured primary CEC, and we provide evidence that G4 stabilization is a novel mechanism regulating the SASP component CCN1.